Do crime hot spots exist in developing countries?: evidence from India - Mazeika, David M. (Journal of quantitative criminology, 2017)
Objectives To determine whether concentrations of crime documented in American cities such as Boston, Jacksonville, Minneapolis, Sacramento, and Seattle generalize to unique environments such as India. Methods Two years of motor vehicle theft (MVT) and burglary incidents from two police stations in Jaipur, India are analyzed. The degree to which crime clusters is documented using nearest neighborhood hierarchical clustering (NNHC). These results are compared to several widely cited studies documenting concentrations in the United States. Results The NNHC procedure identified five MVT hot spots, which accounted for just .09 % of the two station’s land, but over 13 % of these incidents, and four burglary hot spots, which accounted for less than 1 % of its land, but nearly 23 % of the incidents. Conclusions Given the stark differences in the built environment and sociological makeup of Jaipur, a better understanding of the forces that cause crime to concentrate to a high degree needs to be discerned before implementing law-enforcement driven policies derived from the scholarship of American cities. Additional research should also seek to replicate not just the degree to which crime clusters in these unique environments, but also its stability over time and micro place variation.